2003
DOI: 10.1097/01.brs.0000083170.34304.a3
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Sway Measures of Postural Stability During Clinical Balance Tests in Patients With Chronic Whiplash Injury Symptoms

Abstract: Subjects who have a chronic whiplash injury show a characteristic pattern of trunk sway that is different from that of other patient groups with balance disorders. Balance was most unstable during gait involving task-specific head movements which possibly enhance a pathologic vestibulo-cervical interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 18 publications
3
46
1
3
Order By: Relevance
“…Increased magnitude of postural sway is well documented in neck pain sufferers of both traumatic and non-traumatic origin (Dehner et al, 2008;Jull, Sterling, et al, 52 2008; Sjostrom et al, 2003;. As discussed previously, postural control is achieved through the complex process of sensorimotor integration, a process that cervical proprioceptive input contributes substantially.…”
Section: Cervical Spine Manipulation and Postural Swaymentioning
confidence: 96%
See 1 more Smart Citation
“…Increased magnitude of postural sway is well documented in neck pain sufferers of both traumatic and non-traumatic origin (Dehner et al, 2008;Jull, Sterling, et al, 52 2008; Sjostrom et al, 2003;. As discussed previously, postural control is achieved through the complex process of sensorimotor integration, a process that cervical proprioceptive input contributes substantially.…”
Section: Cervical Spine Manipulation and Postural Swaymentioning
confidence: 96%
“…These include nonspecific neck pain Jull, Sterling, et al, 2008;, whiplash (Dehner et al, 2008;Sjostrom et al, 2003;Treleaven, 2007), osteoarthritis (Boucher, Descarreaux, & Normand, 2008) and muscular fatigue Stapley, Beretta, Toffola, & Schieppati, 2006). …”
Section: The Role Of the Cervical Region In The Postural Control Systemmentioning
confidence: 99%
“…Static Balance Several studies have demonstrated disturbed postural stability in individuals with traumatic neck pain, 8,68,95,96 especially in those with symptoms of dizziness. 120 Balance disturbances have also been related to neck muscle fatigue in those with WAD.…”
Section: Standing Balancementioning
confidence: 99%
“…After pain, dizziness and unsteadiness are the next most frequent complaints in those with persistent problems following a whiplash trauma, with up to 70% reporting these complaints (Treleaven et al , 2003). These symptoms are thought to reflect a mismatch of afferent input from the proprioceptive, visual and or vestibular systems to the sensorimotor control system and have been associated with objective deficits in proprioception, head and eye movement control and balance in those with persistent whiplash (Sjöström et al , 2003, Treleaven et al, 2003, Treleaven et al , 2005b). Abnormal cervical afferent input, due to factors such as pain (Le Pera et al, 2001;Thunberg et al, 2001;Flor, 2003), altered neuromotor control (Falla, 2004), muscle fatigue, (Stapley et al 2006) and psychosocial stresses (Passatore and Roatta, 2006), is suggested be one of the main causes of these disturbances (Treleaven., 2008).…”
Section: Introductionmentioning
confidence: 99%